The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1590/s1516-89132009000100022
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of methods for phenotypic stability analysis of cassava (Manihot esculenta Crantz) genotypes for yield and storage root dry matter content

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 20 publications
1
16
0
2
Order By: Relevance
“…Significant interactions between environment and cassava cultivars have been reported by different authors (Rimoldi et al 2003, Kvitschal et al 2007, Kvitschal et al 2009, Costa et al 2013, Santiago et al 2015. The GxE interaction was decomposed by the AMMI into two principal components, but only de first axis was significant based on the F R test (Cornelius et al 1992).…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…Significant interactions between environment and cassava cultivars have been reported by different authors (Rimoldi et al 2003, Kvitschal et al 2007, Kvitschal et al 2009, Costa et al 2013, Santiago et al 2015. The GxE interaction was decomposed by the AMMI into two principal components, but only de first axis was significant based on the F R test (Cornelius et al 1992).…”
Section: Resultsmentioning
confidence: 93%
“…Therefore, the study on both adaptability and stability of genotypes is desirable in order to identify those with the most predictable responses to diverse environments. Among the several methodologies to analyze adaptability and stability (Eberhart and Russel 1966, Lin and Binns 1988, Gauch and Zobel 1996, Toler and Burrows 1998, the multivariate AMMI or Additive Main Effects and Multiplicative Interaction Analysis is the most widely used in Brazil (Carbonell et al 2004, Pacheco et al 2005, Kvitschal et al 2007, Kvitschal et al 2009, Gonçalves et al 2010, Oliveira et al 2010, Mattos et al 2013, Barros et al 2013, Oliveira et al 2014. This method combines analysis of variance and principal components to adjust the main effects (genotypes and environments) and the effects of G×E interactions Vencovsky 2001, Zobel et al 1988).…”
Section: Introductionmentioning
confidence: 99%
“…While UNCA-41 had a purple petiole, dark brown external color of stem and root, yellow color of root pulp, long length, and average diameter of the root, UNCA-39 had yellowish-green petiole, light brown external color of stem and root, cream color of root pulp, average length, and thin diameter of roots. This accession had high average divergence concerning all accessions evaluated, which according to Kvitschal et al (2009) indicate that the accession mentioned above tend to provide a satisfactory heterotic effect when used as parental in a breeding program.…”
Section: Multivariate Analysismentioning
confidence: 83%
“…Similarity, the discrimination of genotypes between these methods was also reported in studies with other crops as observed by Amaral Jr et al (1999) in pumpkin, Simon et al (2012) in maize, Barelli et al (2006) and Teixeira et al (2013) in common bean, and in chili by Leite (2014). Kvitschal et al (2009) also noted similarities between Tocher and UPGMA methods and concluded that, although both have not been identical, one method completes the other.…”
Section: Multivariate Analysismentioning
confidence: 99%
“…YAN et al (2000) acreditam que esta proporcionalidade da resposta de genótipos seja mais lógica e biologicamente plausível, pois há correlação quase perfeita entre o rendimento de grãos e o PC1 (NETO-FRITSCHE et al, 2010;SINEBO et al, 2010). Por outro lado, no modelo AMMI2, tem-se observado correlação negativa entre IPC1 e o rendimento (KVITSCHAL et al, 2009). Entretanto, no modelo AMMI1, há correlação quase v.42, n.8, ago, 2012.…”
Section: Gge Biplot Versusammiunclassified